Analisis Harga Pokok Produksi Menggunakan Metode Full Costing Pada CV Roti Galuh Sari Bogor - Muhammad Rasyiq Taqiyudin Syauqi; Muhammad Ikhsan Al Anshori Hidayat; Maulidiya, Dewi; Yuni Astuti Tri Tartianti (PT Maju Malaqbi Makkarana, 2024)
SMEs are part of the spearhead of the Indonesian economy that has a significant influence, and every SME will be more efficient if they apply the cost accounting method, the cost of production is the scope of cost accounting. The cost of production provides benefits for SMEs to provide information related to costs in production, thus providing data to help management decisions in production. The problem is that there are still many SMEs that have not been able to make the right cost of production for each of their products. This study aims to determine the right cost of production so that SMEs can find out the actual cost of production by calculating production costs. CV Roti Galuh Sari Bogor is used as the analysis material in this study, the study uses a descriptive method with a case study approach, determining the cost of production with the full costing method using primary data obtained from interviews and observations, and secondary data obtained through literature studies. The results of the analysis showed that the production cost in a month costs Rp393,204,472.00 with a cost per tray costing Rp3,231.12. The results of the analysis show that the full costing method can provide an overview of overall production costs, and provide information related to the actual cost of bread production, so that CV Roti Galuh Sari Bogor can find out the HPP of bread products and find out the actual profit.